Uniform Crime Reporting Program Data: Supplementary Homicide Reports, 2009 ([Verlag nicht ermittelbar], 2011)
Since 1930, the Federal Bureau of Investigation has compiled the Uniform Crime Reports (UCR) to serve as a periodic nationwide assessment of reported crimes not available elsewhere in the criminal justice system. Each year, this information is reported in four types of files: (1) Offenses Known and Clearances by Arrest, (2) Property Stolen and Recovered, (3) Supplementary Homicide Reports (SHR), and (4) Police Employee (LEOKA) Data. The Supplementary Homicide Reports provide incident-based information on criminal homicides reported to the police. These homicides consist of murders, non-negligent manslaughter, and justifiable homicides. The data, provided monthly by UCR agencies, contain information describing the victim of the homicide, the offender, and the relationship between victim and offender.